A comparative survey on individuals with prosthesis and without prosthesis - Aralar, Mary Gay; Bautista, Emy Pauline; Francisco, Paulo Eugene; Vergel de Dios, Nanette (Adviser).
A clinical examination was carried out on 18 subjects with removable partial denture, 5 subjects with fixed partial denture and 31 subjects without any form of prosthesis among 20 - 40 year old females in the vicinity of Binangonan, Rizal. (mean age 29.99). A criteria for selection of subjects were set to establish the relationship of having and not having a prosthesis to periodontal health. A series of clinical parameter indices were used to assess the periodontal health status of the subjects, namely the presence of plaque, gingival inflammation and loss of attachment by measuring tooth mobility, probing pocket depth and probing attachment level. Results show that subjects with Removable Partial Denture have consistently higher index values compared to subjects with out prosthesis. This means that our subjects with prosthesis have more gingival inflammation, more plaque accumulation, more attachment loss, more mobility and deeper pocket depths. But only tooth mobility produced a statistically significant value.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Prosthesis; Dentures